2019
DOI: 10.1177/0194599819832277
|View full text |Cite
|
Sign up to set email alerts
|

Epistaxis Risk Associated with Intranasal Corticosteroid Sprays: A Systematic Review and Meta‐analysis

Abstract: Objective Intranasal corticosteroids (INCSs) are widely utilized for the treatment of allergic rhinitis. Epistaxis is a known adverse effect of INCSs, but it is not known if the risk of epistaxis differs among INCSs. Data Sources Systematic review of primary studies identified through Medline, Embase, Web of Science, PubMed Central, and Cochrane databases. Review Methods Systematic review was conducted according to the PRISMA standard. English-language studies were queried through February 1, 2018. The search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 86 publications
1
14
1
Order By: Relevance
“…Their meta-analysis showed that the risk of epistaxis was higher in the INCS group (RR 2.74; 95% CI, 1.88-4.00; n = 2508) as compared with placebo and no intervention. 65 The increased risk of epistaxis with the use of INCS versus placebo is also consistent with findings from Wu et al, 66 who performed a systematic review of the literature related to epistaxis and the use of INCS in patients with AR. The authors performed a meta-analysis of 72 articles, for which the overall RR was 1.48 (95% CI, 1.32-1.67; I 2 0%).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Their meta-analysis showed that the risk of epistaxis was higher in the INCS group (RR 2.74; 95% CI, 1.88-4.00; n = 2508) as compared with placebo and no intervention. 65 The increased risk of epistaxis with the use of INCS versus placebo is also consistent with findings from Wu et al, 66 who performed a systematic review of the literature related to epistaxis and the use of INCS in patients with AR. The authors performed a meta-analysis of 72 articles, for which the overall RR was 1.48 (95% CI, 1.32-1.67; I 2 0%).…”
Section: Discussionsupporting
confidence: 84%
“…68,69 Ciclesonide hydrofluoroalkane, mometasone furoate, and fluticasone propionate have been shown to have very low systemic bioavailability, reducing the total amount of systemic corticosteroids when used in combination with inhaled steroids. 66,69 In fact, Sheth et al 70 performed 2 parallel-group double-blind RCTs comparing oral inhaled fluticasone propionate alone with oral inhaled fluticasone propionate and intranasal fluticasone propionate and did not find an increased risk of adrenal suppression. Based on this information, we suggest that thoughtful discretion be exercised in the use of concomitant nasal and inhaled corticosteroid agents.…”
Section: Discussionmentioning
confidence: 99%
“…INCS are not systemically absorbed; therefore, there are no systemic adverse effects. The most common INCS adverse effects are local, including nasal irritation, stinging and epistaxis 111 , and can usually be prevented by aiming the spray slightly away from the nasal septum. Long-term INCS use does not damage nasal mucosa or induce glaucoma 112 , and growth effects in children seem to be minimal 78 .…”
Section: Box 1 | Managing Patients With Ar During the Covid-19 Pandemicmentioning
confidence: 99%
“…Local irritation and dryness of the nose and throat and sneezing after administration are common local side effects of INCs 24,25 . All INC sprays are associated with a significantly increased risk of epistaxis compared with placebo or no intervention, according to two reviews with relative risk 1.48 (95% CI: 1.32–1.67, 72 studies) and risk ratio 2.74 (95% CI: 1.88–4.00, 2508 participants, 13 studies), respectively 26,27 . In the Cochrane review, the number needed to harm (NNH) can be extracted (NNH = 20 [95% CI: 12–49]) 27 .…”
Section: Efficacy and Safety Of Intranasal Corticosteroidsmentioning
confidence: 99%